Escritores, congressos e meio intelectual em Fortaleza (1942-1946) - Linhares, Francisco David Botelho (2018)
The present research aims to analyze the status of writers of Ceará in the intellectual environment of Fortaleza city in the 1940s, in particular between the years of 1942 and 1946, when it was organized the I Poetry Congress of Ceará (1942) and the I Writers Congress of Ceará (1946). We intend to understand the motivations of this intellectuals group in the accomplishment of both congresses, detecting the agenda items and interests raised, such as the role of the writer in the contemporary world, his/her appreciation, the importance of the copyright and the government support to the publication and promotion of his/her works. Furthermore, this study aims to comprehend the stance of this intellectuals group in the face of social, political and economic changes of the 40s. In order to a better research of such context, it was analyzed memories, news, reports, reviews and literary critics of wide circulation journals in the capital of Ceará, as well as the expert literary magazine, such as the Revista Clã, with the goal of investigating mobility network and sociability in the intellectual environment of Fortaleza.